Theory of the democratic Constitution - Gonzales Ojeda, Magdiel (2020)
The article carries out a detailed study on the conception and delimitation of the Political Constitution of the State. This is based on an analysis of the different meanings established in constitutional literature, from Aristotle to its contemporary development, to then establish the characters and finally, focus, on constitutional supremacy, a special and essential characteristic of the rigid Constitution of a State.